(untitled) (Research, Society and Development, 2022)
Systems stabilized by surfactants in order to incorporate different substances at their interfaces, such as hydrophilic polymers and active compounds, are systems capable of establishing vector control of Aedes aegypti. The system was obtained through the surface tension of PPG-5-CETETH-20/calcium chloride dispersion at concentrations of 0.2%, 0.4%, 0.8%, 1% and 2%, determining the CMC of each sample. Then, a binary study was performed and the system structures were evaluated by Polarized Light Microscopy (PLM) and rheological analysis. Biological analysis was performed to assess the mean lethal concentration (LC50) against Aedes aegypti larvae and toxicity to non-target organisms in Artemia salina. In this sense, the objective of this work was to evaluate the influence of calcium chloride on the behavior of phases and on the biological activity of formulations based on the self-aggregation of surfactants, an alternative larval insecticide to be used as a replacement for larval insecticides already on the market.